The development of murine bone marrow-derived mast cells expressing functional human MRGPRX2 for ex vivo and in vivo studies - Bawazir, Maram; Roy, Saptarshi; Ali, Hydar (Frontiers in Immunology, 2024)
IntroductionA subtype of human mast cells (MCs) found in the skin and to a lesser extent in the lung and gut express a novel G protein-coupled receptor (GPCR) known as Mas-related GPCR-X2 (MRGPRX2, mouse counterpart MrgprB2). In addition to drug-induced pseudoallergy and cutaneous disorders, MrgprB2 contributes to ulcerative colitis, IgE-mediated lung inflammation and systemic anaphylaxis. Interestingly, most agonists activate MRGPRX2 with higher potency than MrgprB2. In this study, we sought to replace mouse MrgprB2 with human MRGPRX2 and to study receptor function ex vivo and in vivo.MethodsMrgprB2−/− bone marrow (BM) cells were transduced with retrovirus encoding MRGPRX2 and differentiated into BMMCs (MRGRPX2-BMMCs) ex vivo. Cell surface MRGPRX2 expression was determined by flow cytometry. Effects of substance P (SP) and LL-37 on Ca2+ mobilization, degranulation and TNF-α generation were determined. MRGPRX2-BMMCs were engrafted intraperitoneally into MC-deficient Wsh/Wsh mice. After 6–8 weeks, immunofluorescence staining was performed on peritoneal lavage cells (PLCs), and sections of small intestine and colon with anti c-Kit and anti-MRGPRX2 antibodies. SP-induced degranulation in PLCs obtained from engrafted mice was determined.ResultsMRGPRX2-BMMCs expressed cell surface MRGPRX2 and responded to both SP and LL-37 for Ca2+ mobilization, degranulation and TNF-α generation. Furthermore, Wsh/Wsh mice engrafted with MRGPRX2-BMMCs expressed the receptor in peritoneal, intestinal and colonic MCs. In addition, PLCs from engrafted mice responded to SP for degranulation.ConclusionReplacing mouse MrgprB2 with functional human MRGPRX2 in primary BMMCs and their engraftment in MC-deficient mice demonstrated the expression of this receptor in different tissues, which provides unique opportunities to study receptor signaling ex vivo and disease phenotype in vivo.